2018
DOI: 10.1007/s00066-018-1356-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of patients after ipilimumab and hypofractionated brain radiotherapy for brain metastases of malignant melanoma: sequence matters

Abstract: PurposeSince the introduction of ipilimumab (IPI) for the treatment of patients with metastatic malignant melanoma, we have observed remarkable responses after hypofractionated whole brain irradiation (WBRT) or stereotactic radiotherapy (STX) for brain metastases of malignant melanoma. We sought to investigate the impact of the sequence of these treatment modalities.MethodsWe retrospectively evaluated the survival of melanoma patients with brain metastases who were treated with WBRT or STX and received IPI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…Similarly, the majority of currently ongoing trials employ concurrent use. By contrast, Schmidberger et al [34] pointed out in their retrospective analysis of 41 melanoma patients with brain metastasis that applying RT before immunotherapies prolonged survival. They showed that patients treated with ipilimumab after RT had a median survival of 11 months, compared with three months for the patients who received ipilimumab prior to RT.…”
Section: Reviewmentioning
confidence: 97%
“…Similarly, the majority of currently ongoing trials employ concurrent use. By contrast, Schmidberger et al [34] pointed out in their retrospective analysis of 41 melanoma patients with brain metastasis that applying RT before immunotherapies prolonged survival. They showed that patients treated with ipilimumab after RT had a median survival of 11 months, compared with three months for the patients who received ipilimumab prior to RT.…”
Section: Reviewmentioning
confidence: 97%
“…Tumor xenograft models and treatment regimens MDA-MB-231 cells (1×10 7 ) or triple negative breast cancer (TNBC) patient-derived tumor xenograft (PDTX) tissues were subcutaneously implanted into the right flank of NSG or humanized NSG mice. When tumors reached 80-100 mm 3 , mice were treated with either phosphate buffered saline (PBS) or anti-PD-1 monoclonal antibody (BE0188, clone J116, Bioxcell, New Hampshire, USA) of 200 µg/mouse by intraperitoneal injection, every 3 days, up to six times. The tumor size was measured every 2 or 3 days using a caliper, and tumor volumes were calculated using the modified ellipsoid formula (1/2 × (length × width 2 ).…”
Section: Materials and Methods Micementioning
confidence: 99%
“…A retrospective analysis of patients treated for brain metastases of malignant melanoma revealed that inhibition of the PD-1 axis was more effective than inhibition of CTLA-4 in combination with external beam radiotherapy and that concurrent dosing (at least 4 weeks within the two treatments) was necessary to induce best responses [163]. Independent retrospective studies and one meta-analysis confirmed these results [145,[164][165][166][167][168][169][170][171] (Table 4), also showing the superiority of combining radiation with PD-1 inhibitors compared to combination with other agents such as v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) or dual specificity mitogen-activated protein kinase kinase (MEK) inhibitors [172,173] (Table 4). One retrospective study showed longer overall survival of patients irradiated more than 16 weeks after initiation of ipilimumab, compared to patients irradiated within 16 weeks of starting ipilimumab treatment [174].…”
Section: Current Clinical Insights On Irradiation and Immune Checkpoimentioning
confidence: 95%